Correction of Femoral Valgus Deformity - van Heerwaarden, Ronald; Brinkman, Justus-Martijn; Pronk, Yvette (The Journal of Knee Surgery, 2017)
In the past two decades, the insights in the causes and development of valgus leg deformities as well as the options for treatment with corrective osteotomies have dramatically changed. New definitions for deformity analysis and planning for corrections have better defined the patients suitable for femoral valgus deformity corrections. Biomechanical research on new osteotomy methods and stability of plate fixation have provided scientific background for the development of improved surgical techniques that are more accurate, safer, and provide for quicker rehabilitation and bone healing. This article provides an overview of the basic principles behind the correction of femoral valgus deformity. Both the analysis and planning of femoral valgus deformity correction as well as the results of systematic clinical reviews are provided. The current recommended surgical technique of biplanar medial closing-wedge supracondylar osteotomy is explained, and the first clinical results are reported. Finally, the authors describe some of the future directions and needs for treatment optimization of patients with femoral valgus deformity.
Keywords: closing-wedge osteotomy; supracondylar osteotomy; valgus leg correction